Noninvasive Imaging to Evaluate Women With Stable Ischemic Heart Disease - Baldassarre, Lauren A. (JACC Cardiovasc Imaging, 2016)
Declines in cardiovascular deaths have been dramatic for men but occur significantly less in women. Among patients with symptomatic ischemic heart disease (IHD), women experience relatively worse outcomes compared with their male counterparts. Evidence to date has failed to adequately explore unique female imaging targets and their correlative signs and symptoms of IHD as major determinants of IHD risk. We highlight sex-specific anatomic and functional differences in contemporary imaging and introduce imaging approaches that leverage refined targets that may improve IHD risk prediction and identify potential therapeutic strategies for symptomatic women.